Nitrogen evolution, NOX formation and reduction in pressurized oxy coal combustion. (April 2022) - Rahman, Zia ur; Wang, Xuebin; Zhang, Jiaye; Yang, Zhiwei; Dai, Gaofeng; Verma, Piyush; Mikulcic, Hrvoje; Vujanovic, Milan; Tan, Houzhang; Axelbaum, Richard L.
Abstract: Oxy-combustion is one of the most prominent solutions for reducing CO2 emissions from coal-fired power plants using carbon-capture-and-utilization technology. However, when compared to air combustion at atmospheric pressure, oxy-combustion is very expensive, owing to the significant efficiency penalties associated with air separation, flue gas recirculation (FGR), treatment, compression, and storage or transit of CO2 . In comparison, pressurized oxy-combustion (POC) is more efficient as it recovers a significant amount of heat energy from the flue gas moistures. Nevertheless, CO2 derived from pressurized oxy coal combustion has impurities, e.g., acid gases (NOX and SOX ) that can corrode the plant equipment, transport lines as well as deteriorating effect on the environment. Fortunately, in pressurized combustion systems, both NOX and SOX can be scrubbed by a single-column direct contact cooler (DCC), but this requires a minimum ratio of NOX to SOX at the inlet to be efficiently removed. Therefore, NOx is one of the important hindering parameters in commercializing the pressurized oxy-combustion. Although NOx evolution during oxy-coal combustion has been explored extensively at 1 atm, higher pressure studies are rare. Much still needs to be done to better understand the NOX mechanism and the effects of different parameters on NOX emissions under these conditions. This paper reviews the published literature on nitrogen evolution, NOX formation and reduction in pressurized oxy-coal combustion. At higher pressures, the NOX from fuel-bound nitrogen is generated through volatiles, tar and char, all of which are discussed. Where literature is not available, the effect of pressure on NOx evolution in different stages of coal combustion is predicted through CHEMKIN simulation. Homogeneous and heterogeneous pathways of NOX formation and their destruction in pressurized oxy-coal combustion are evaluated. Additionally, the effect of pressure on a few mature and commercialized NOx abatement methods is explored. In the last, the future perspective and recommendation are given. This review will aid in the provision of basic knowledge about NOx evolution and control in pressurized fuel combustion, as well as the identification of new research areas to pursue. Graphical abstract: Image 1 Highlights: Volatile-N decreases with increasing pressure and increases with heating rate. Elevated pressure strengthens the gasification of CO2 to CO. The de-NOx efficiency of SNCR and reburning enhanced at higher pressure. Conversion of NO to NO2 is improved at elevated pressure. High pressure upgrades the heterogeneous NOx reduction with char.